Hidden Fossils of The Hondsrug Complex Connect Time and Space - Margaretha Roelfs; Harry Huisman (Geoconservation Research)
The Hondsrug UNESCO Global Geopark in the northeast of the Netherlands comprises the Hondsrug-complex, a prominent range of low till ridges created by forces of moving land ice and melt water. The unusual orientations of the ridges contrast with the usual direction of ice flow, and they are separated from each other by elongate depressions. The area shows a strong cultural history, in which neanderthals encamped about 50,000 years ago, reindeer hunters roamed, and the area is famous for dozens of dolmens, burial mounds and prehistoric Celtic fields. The land ice left behind thick layers of till, scattered with billions of erratic boulders that often contain fossils. But this is a special case because the fossils are ‘hidden’ in erratic blocks, and testify to Earth history thousands of miles north in the Baltic Sea and millions of years earlier, in the Paleozoic. The Geopark can teach not only the local geological, cultural and natural heritage but also geology and life far beyond.